Legal Policy on The Evidentiary Status of IP Addresses in Government Tender Collusion - Khalid Mustafa; I Gede Agus Kurniawan; Ruetaitip Chansrakaeo (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2025)
This research aims to analyze the position of IP Address in evidentiary law related to government tender collusion and to formulate the direction of legal policy for its regulation in Indonesia. The research results show that an IP Address has legitimacy as part of electronic evidence based on the Electronic Information and Transactions Law, but it does not have absolute evidentiary power because it only indicates a technical relationship between electronic activities and certain devices or networks. In the case of tender collusion, an IP Address is more accurately classified as circumstantial evidence or corroborative digital evidence that must be supported by metadata, system logs, affiliation relationships, electronic communications, and digital forensic results. This research also found the fragmentation of regulations and the absence of digital evidence standards, which lead to inconsistencies in the application of the law. Therefore, legislative reform is needed thru amendments to Law Number 5 of 1999, strengthening KPPU Regulations, and harmonization with the Electronic Information and Transactions Law, the Personal Data Protection Law, and government procurement regulations. The reform must be based on the principles of integrity, authenticity, chain of custody, due process of law, risk-based enforcement, and digital evidence governance to achieve legal certainty, the effectiveness of competition law enforcement, and transparent, accountable, and integrity-based government procurement governance.